A Modified Method for DNA Extraction From Buccal Cells for Genetic Epidemiological Studies Among Children - Escobar de González, Wendy Yesenia; Aguirre de Rodríguez, Katleen Argentina; Castañeda Monroy, Vianney; Patiño-Marín, Nuria; Medina-Solís, Carlo E; Niño-Martínez, Nereyda; Terán-Figueroa, Yolanda (Curēus (Palo Alto, CA), 2024)
In large-scale molecular studies, a protocol that generates high yields and quality DNA for future polymerase chain reaction (PCR) assays is needed. The collection of buccal cells by cytobrush may represent an efficient, noninvasive, and inexpensive method for obtaining genetic material from school populations. The aim of this study was to develop a method to obtain genomic DNA from buccal cells of schoolchildren, and the DNA was extracted immediately after collecting the buccal cell samples and after storing the samples for 8 months at -20 °C to establish the feasibility of the method for epidemiological studies. Forty-five Salvadoran schoolchildren aged between seven and fifteen years participated. Two samples of buccal cells were collected with cytobrush from each subject. The yield of the extracted DNA was evaluated by spectrophotometry, and purity was measured using optical density (OD) 260/280. The functional quality was assessed by PCR and established by amplifying the 536 bp region of the gene. The yield was 65.70 μg for the immediate extraction group and 47.63 μg for the extraction group after eight months of storage at -20°C. The purity measured was 2.0 for immediate extraction and 1.9 for extraction after eight months. The functional quality was greater than 90% for both groups. This protocol can be used to obtain DNA of high yield, purity, and functional quality from schoolchildren for genetic epidemiological studies based on PCR. This method is effective whether DNA is extracted immediately after collection or after buccal cell samples have been stored at 20°C for eight months.